Analisis Permasalahan Dalam Pembelajaran Daring Masa Pandemi Covid-19 - Gamar Al Haddar; Afdal; Septyana Puspita Ningrum (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
This research is motivated by the existence of problems in learning that is carried out online or online, this learning is carried out because it is to prevent the transmission of covid-19 that is happening at this time. This type of research is qualitative. Testing the validity of the data by triangulation of sources. The results of the research on problem analysis in online learning for class II D students during the covid-19 pandemic at SDN 024 North Samarinda for the 2020/2021 academic year. First, the implementation of online learning for class II D students at SD Negeri 024 North Samarinda in 2020/2021 has not gone as expected because the teacher only provides material and assignments during the online learning process even though it is via mobile phones by using the WhatsApp application only. The problems faced during the online learning process at SD Negeri 024 North Samarinda are the lack of teacher competence regarding technology, the level of understanding of students when carrying out the online learning process, less varied learning, limited cellphone facilities such as parents who do not have smartphones, cellphones that do not support , lack of use of facilities and infrastructure, internet packages that cannot be reached by all students, lack of a sense of student discipline, and students not focusing on studying at home. Thus, teachers should master technology so that online learning can be understood by students and does not make it boring even without meeting face to face.